Analysis of Flexural Toppling Failure in Rock Slopes Using Discrete Element Method - Zheng, Yun; Wang, Runqing; Chen, Congxin; Meng, Fei (Frontiers in Earth Science, 2021)
Flexural toppling failure is a common failure mode of natural and artificial rock slopes, which has caused serious damage to human life and property. In this work, an advanced numerical method called the Universal Distinct Element Code (UDEC) was used to study the mechanism of flexural toppling failure. In total, more than twenty slope models were built and analyzed. Two new parameters (displacement discontinuity and transition coefficient of failure surface) were introduced to present a further understanding of flexural toppling. The results show the failure zone of rock slopes subjected to flexural toppling includes two parts: the first-order instability part (FOIP) and the independent toppling zone (ITZ). The FOIP can be further divided into two subzones: the sliding zone (SZ) and the superimposed toppling zone (STZ). The occurrence of surface deformation discontinuities is the precursor to flexural toppling failure. The first displacement discontinuity occurs on the boundary between the FOIP and the ITZ. The angle, spacing, and angle of the joints, the angle of the slope has a significant influence on the stability of anti-dip bedding rock slopes. However, they do not affect the deformation and failure pattern of the slope.